JUDICIAL REVIEW OF PERPETRATORS REGARDING CRIMES OF VIOLENCE IN THE FAMILY - Simanjuntak, Immanuel; Sari Br Malau, Eka Agustina; Lase, Severtianus; Sagala, Christian Raja Adi Negara; Agus , Azwir (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
Domestic Violence (KDRT) is a problem related to violence that often occurs in households and enters into issues regarding Human Rights (HAM). know the form of criminal responsibility towards the perpetrators of cases of criminal acts of violence in the family, as well as the views of judges on this matter. The normative research method with a qualitative approach is used in this study. Criminal responsibility for the perpetrators of the decision Number 2138/Pid,sus/2019/PN.Mdn that the perpetrators based on the crime that the perpetrators committed violated Article 44 paragraph 1 (one) of Law No.23 of 2004 concerning the Elimination of Domestic Violence, where in this case the perpetrator is asked for criminal responsibility as a legal subject.